Migration from Epi Info to District Health Information Software 2 for vaccine-preventable disease surveillance - WHO African Region, 2019-2023. - Adegoke, Oluwasegun Joel; Rachlin, Audrey; Porter, Angela Montesanti; Katsande, Reggis; Kubenga, Steve; Potter, Rebecca; Titlestad, Ola Hodne; Noubi Tchoupopnou, Lucie Royd; Rosencrans, Louie; Kinkade, Carl; Crispino, Vittoria; Shragai, Talya; et al. (Weekly Epidemiological Record, 2024)
High-quality data from surveillance of vaccine-preventable disease (VPD) are critical for timely detection of and response to outbreaks. In 2019, the World Health Organization (WHO) Regional Office for Africa (AFRO) began a change from Epi Info, a statistical software package developed by the US Centers for Disease Control and Prevention (CDC), with limited capability to integrate with other information systems, affecting reporting timeliness and data use, to the District Health Information Software 2 (DHIS2), a free, open-source software platform for electronic aggregate Integrated Disease Surveillance and Response (IDSR) and case-based surveillance reporting. A national reporting system was introduced to allow countries to adopt this system. Regionally, the Epi Info database will be replaced by a DHIS2 regional data platform. This report describes phased implementation from 2019 to the present. Phase 1 (2019-2021) involved developing IDSR aggregate and case-based surveillance packages and pilot studies in Mali, Rwanda and Togo. Phase 2 (2022) included extending national implementation to 27 countries and establishing the WHO AFRO DHIS2 regional data platform. Phase 3 (from 2023 onwards) comprised building local capacity and support for national reporting to the regional platform. By February 2024, 8 of 47 AFRO countries had adopted both the aggregate IDSR and case-based surveillance packages, and 2 had successfully transferred VPD surveillance data to the AFRO regional platform. The challenges included limited human and financial resources, establishment of data-sharing and governance agreements, technical support for data transfer, and building local capacity to report to the regional platform. Transition to DHIS2 will ensure efficient data transmission to strengthen detection and response of VPD and public health emergencies through greater system integration and interoperability.